Relationship between subjectively-rated and objectively-tested physical function across six different medical diagnoses - Thomas Benz; Susanne Lehmann; Peter S. Sandor; Felix Angst (Medical Journals Sweden, 2023)
Objective: To quantify and compare associations and relationships between self-rated and tested assessments of mainly mobility-related physical function in different diagnoses. Design: Six longitudinal cohort studies before and after inpatient rehabilitation. Patients: Patients with whiplash-associated disorder (n = 71), low back pain (n = 121), fibromyalgia (n = 84), lipoedema (n = 27), lymphoedema (n = 78), and post-acute coronary syndrome (n = 64). Methods: Physical function was measured with the self-rated Short-Form 36 Physical functioning (SF-36 PF) and with the tested 6-Min Walk Distance (6MWD) and assessed by correlation coefficients. Across the 6 cohorts, the relationship between the 2 scores was compared using the ratio between them. Results: The correlations between the 2 scores were mostly moderate to strong at baseline (up to r = 0.791), and weak to moderate for the changes to follow-up (up to r = 0.408). The ratios SF-36 PF to 6MWD were 1.143-1.590 at baseline and 0.930-3.310 for the changes, and depended on pain and mental health. Conclusion: Moderate to strong cross-sectional and moderate to weak longitudinal correlations were found between the 6MWD and the SF-36 PF. Pain and mental health should be considered when interpreting physical function. For a comprehensive assessment in clinical practice and research, the combination of self-rated and tested physical function measures is recommended.